Hatchery Management of Major Cultivable Fin-Fishes - Rana Rushirajsinh Jitendrasinh; A. S. Kotiya; K. H. Vadher (Newest Updates in Agriculture and Veterinary Science Vol. 3, 2023)
The importance of captive breeding and hatchery management assumes greater significance in increasing finfish production. This chapter has been structured to give an overview of the natural breeding habitats of finfish from riverine sources and seed collection from riverine as well as brackish water sources. The importance of hydrological and hydro-biological factors in relation to the natural breeding of finfish has been dealt with in detail. The sexual maturity and breeding seasons of various cultivable species emphasizing the development of gametes in male and female fishes have been dealt with. Different methods of breeding finfish. Induced breeding of fin fishes, the effect of environmental factors on spawning has been explained. Different aspects of management of broodstock.